Examining the Appropriateness of Betawi Folklore as Literacy Reading Materials for Elementary Schools - Hidayatullah, Syarif; Komara, Cahya (JOLLT Journal of Languages and Language Teaching, 2025)
Betawi folklore holds great potential as both a didactic and creative medium. Integrating Betawi folklore into literacy reading materials for elementary school students can yield positive educational benefits. However, due to the diversity of Betawi folklore, teachers must carefully select appropriate stories and implement effective learning strategies to ensure educational objectives are met. This study examines the appropriateness of Betawi folklore as literacy reading material for elementary school students. Employing a qualitative research approach, it utilizes content analysis techniques to assess intrinsic literary elementsâ€”such as themes, plots, characters, and settingsâ€”based on children’s literature principles and cognitive development theories, particularly Piaget’s concrete operational stage. The primary data sources include Cerita Rakyat Betawi 1 and Cerita Rakyat Betawi Â by Rahmat Ali. To validate the content analysis findings, teachers were asked to evaluate the suitability of Betawi folklore through a questionnaire.Â The results indicate that teachers must exercise careful selection, as not all Betawi folklore align with children’s literature criteria and cognitive development stages. This study recommends strategies for adapting Betawi folklore to enhance its suitability for literacy activities in elementary schools.